Demotivational Factors among Secondary School EFL Teachers in Iran (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Demotivating factors negatively influence teachers attitudes and behaviors and hence lead to undesired teaching outcomes. The endeavor of this thesis was to scrutinize some sources of demotivational factors among Iranian English language teachers junior and senior high schools. To begin with, 100 junior and senior high school teachers in Chaharmahal Va Bakhtiari province, South West of Iran participated in this study. Two instruments (questionnaire and interview) were used for collecting data. Descriptive and inferential statistics for all questions and categories were generated and reported. The overall results showed that five out of six top items are related to working conditions and class facilities. The lowest number of demotivating factors related to lack of communication among teachers, lack of expression of straight opinion by colleagues, heterogeneity of learners in one class, students' forgetting to do homework, students' forgetting to bring textbook. The results also showed that recognizing and eradicating such impeding factors serve promising attention to learning, teaching and attainment.